Computational science and engineering: a new master’s program at the Technische Universität München - Bungartz, Hans-Joachim (Future generation computer systems, 2003)
In the winter semester of 2001/2002, the Technische Universität München (TUM) started its new master’s program computational science and engineering (CSE) as a joint initiative of seven faculties. It is the objective of this contribution to outline the underlying ideas and concepts and their curricular implementation as well as to emphasize some features that are probably non-standard in other comparable programs.